MASYARAKAT KELAS BAWAH DALAM LIRIK LAGU-LAGU IWAN FALS (1981-1994) - Wahyudin, Wahyudin; Absor, Nur Fajar (Estoria: Journal of Social Science and Humanities, 2022)
Abstract This article discusses Iwan Fals' musical career and his songs with the theme of social criticism, especially songs with the theme of lower class society from 1981-1994. The purpose of this article is to explain the meaning or content contained in the lyrics of Iwan Fals' songs with the theme of lower class society which will then be linked to the context of society at that time. This article uses the Historical method which is presented in a descriptive-analytical form and utilizes news sources, cassette covers, newspapers and magazines, photos and relevant books. To examine the lyrics of the song specifically using the semiotic method of Roland Barthes. Based on the facts collected, Iwan Fals is a stage name and has the real name virgiawan listanto. As a child, he often played with poor children in the village behind his house. He began to recognize music from his boarding house in Bandung. His success in winning the 1979 Country Music Festival made Musica Studio recruit Iwan Fals. Together with musica he completed 13 albums between the period 1981-1988.Iwan Fals considers his songs are the result of his observations of society. From the results of the analysis, Iwan Fals' songs have a lot to say about the life of the lower class. His partiality to the lower class of society is inseparable from his background in life which is close to the community. Keywords: Iwan Fals, Lower Class Society, Music Industry, Semiotics